High-frequency lacustrine sequence stratigraphy of clastic lakes: lessons from ancient successions - Zavala, Carlos Alberto (2024)
Sequence stratigraphic concepts and methods provide novel tools for performing stratigraphic analysis, allowing us to improve our understanding of depositional models and basin evolution. Main controls and depositional elements (e.g., surfaces, systems tracts, parasequences, etc.) recognized in conventional sequence stratigraphy are designed for marine-related systems. In contrast, the sequence stratigraphy of lacustrine successions is much more complex and poorly understood, because it is not driven by sea-level changes, but by a complex interaction between tectonics and high-frequency climatic cycles. The comprehensive analysis of the water balance of lacustrine systems allows the recognition of three types of lake conditions: Underfilled, balanced-fill and overfilled lakes. Understanding the lake conditions in ancient successions is fundamental for unraveling lacustrine sequence stratigraphy, since these conditions effectively control water salinity, internal stacking pattern and the characteristics of systems tracts. Underfilled lakes are hydrologically closed lakes, and consequently, the lake-level can highly fluctuate, driven by high-frequency wet-dry climatic cycles. During wet periods, rivers supply water and sediments, resulting in fining-and thinning-upward elementary depositional sequences (EDS’s) accumulated during the transgressive systems tract (TST). In contrast, dry periods are characterized by a relative lake-level fall with the subaerial exposure of lake margin areas during the regressive systems tract (RST). Lake water salinity can fluctuate from brackish to hypersaline. Balanced-fill lakes are partially closed lakes, and consequently, they have characteristics of both underfilled and overfilled lakes. During the TST, the lake is in underfilled condition, and consequently, the introduction of water and sediment will accumulate a fining-upward interval until reaching the spill point during the maximum flooding. The RST is accumulated under an overfilled lake condition, with coarsening-upward progradational littoral deltas and related subaqueous delta deposits. Lake water salinity fluctuates from brackish to freshwater. Overfilled lakes are hydrologically open lakes. Most deposits accumulate during the RST, forming coarsening-upward progradational littoral deposits, with associated subaqueous deltas. All overfilled lakes are freshwater lakes. Subsidence is crucial for allowing the long-term preservation of lacustrine deposits. Lakes can temporarily store water and sediments in areas that lack subsidence, but these deposits will not be preserved in the stratigraphic record. Consequently, two types of lakes are recognized: 1) subsiding lakes, which have permanent accommodation space and 2) hanging lakes, having temporary accommodation space. Although they cannot permanently store sediments, hanging lakes are fundamental for lacustrine sequence stratigraphy, since they can flood subsiding lakes with the near-instantaneous release of a substantial volume of water, creating favorable conditions for the accumulation of organic-rich shales. This rapid flooding from hanging lakes induced a forced transgression (FT), which is a large-scale rapid transgression (xenoconformity) not related to the normal sediment and water supply from local source areas.